Quality of latin american universities in the light of international academic rankings; Qualidade das universidades latino-americanas a luz dos rankings acadêmicos internacionais; Calidad de las universidades latinoamericanas a la luz de los rankings académicos internacionales - Abello-Romero, J (Fundacao Cesgranrio, 2026)
University rankings have become instruments providing information guiding various stakeholders in their decision-making processes, based on indicators that may approximate quality assurance mechanisms. Latin American universities were analyzed in light of major international rankings to study convergences in terms of institutional quality, based on their respective performances. This involved a bibliographic and documentary investigation, including the analysis of performance indicators from the Times Higher Education, QS World University Rankings, and Academic Ranking of World Universities, along with data collected from governmental bodies. It was found that few Latin American universities stand out internationally; however, some convergences were observed in the cases of Argentine, Brazilian, Chilean, Colombian, and Mexican institutions. © 2026 Fundacao Cesgranrio. All rights reserved.
Keywords: Academic Rankings; Higher Education; Latin America; Quality Indicators; Quality of Education